ASAH1 pathogenic variants associated with acid ceramidase deficiency: Farber disease and spinal muscular atrophy with progressive myoclonic epilepsy. Issue 9 (24th June 2020) - Elsea, Sarah H.; Solyom, Alexander; Martin, Kirt; Harmatz, Paul; Mitchell, John; Lampe, Christina; Grant, Christina; Selim, Laila; Mungan, Neslihan Oneli; Guelbert, Norberto; Magnusson, Bo; Sundberg, Erik; et al.
Abstract: Farber disease and spinal muscular atrophy with progressive myoclonic epilepsy are a spectrum of rare lysosomal storage disorders characterized by acid ceramidase deficiency (ACD), resulting from pathogenic variants in N‐acylsphingosine amidohydrolase 1 ( ASAH1 ). Other than simple listings provided in literature reviews, a curated, comprehensive list of ASAH1 mutations associated with ACD clinical phenotypes has not yet been published. This publication includes mutations in ASAH1 collected through the Observational and Cross‐Sectional Cohort Study of the Natural History and Phenotypic Spectrum of Farber Disease (NHS), ClinicalTrials.gov identifier NCT03233841, in combination with an up‐to‐date curated list of published mutations. The NHS is the first to collect retrospective and prospective data on living and deceased patients with ACD presenting as Farber disease, who had or had not undergone hematopoietic stem cell transplantation. Forty‐five patients representing the known clinical spectrum of Farber disease (living patients aged 1–28 years) were enrolled. The curation of known ASAH1 pathogenic variants using a single reference transcript includes 10 previously unpublished from the NHS and 63 that were previously reported. The publication of ASAH1 variants will be greatly beneficial to patients undergoing genetic testing in the future by providing a significantly expanded reference list of disease‐causing variants. Abstract : Farber disease and spinal muscular atrophy with progressive myoclonic epilepsy are a spectrum of rare lysosomal storage disorders characterized by acid ceramidase deficiency (ACD), resulting from pathogenic variants in N‐acylsphingosine amidohydrolase 1 (ASAH1). We provide a comprehensive assessment of variants in ASAH1 collected through the Observational and Cross‐Sectional Cohort Study of the Natural History and Phenotypic Spectrum of Farber Disease (NHS), ClinicalTrials.gov identifier NCT03233841, in combination with an up‐to‐date curated list of published mutations describing the spectrum of ACD.